2011
DOI: 10.4314/ajpherd.v17i3.68075
|View full text |Cite
|
Sign up to set email alerts
|

Life skills as predictors of engagement in health risk behaviours: A survey of secondary school learners

Abstract: There is consensus that education on the prevention of health risk behaviour and an increased repertoire of life skills could facilitate a reduction in health risk behaviours. This article reports on the results of a survey among 1027 grades 8-10 learners aged 13-18 years and profiles their engagement in smoking, drug use, drinking and sexual activity. It reports on the hypothesis testing for the relationship between life skills, as measured by the Life Effectiveness Questionnaire (LEQ), and engagement in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…All these skills fall into the category of life skills, which are defined as a group of psychosocial competencies and interpersonal skills that help people make informed decisions, solve problems, think critically and creatively, communicate effectively, build healthy relationships, empathize with others, and cope with and manage their lives in a healthy and productive manner (WHO, 2003). In general, the adoption of relevant life skills leads to healthy lifestyles and the prevention of risk behaviors or other mental and somatic health problems (Manee, Khouiee, & Zaree, 2011; Pharaoh, Frantz, & Smith, 2011). Although we can find many recommendations in the literature on how specific skills should be developed to prevent Internet addiction, there is only one study (Xu, Turel, et al., 2012) that evaluated the impact of some specific skills in the prevention of Internet addiction.…”
Section: Discussionmentioning
confidence: 99%
“…All these skills fall into the category of life skills, which are defined as a group of psychosocial competencies and interpersonal skills that help people make informed decisions, solve problems, think critically and creatively, communicate effectively, build healthy relationships, empathize with others, and cope with and manage their lives in a healthy and productive manner (WHO, 2003). In general, the adoption of relevant life skills leads to healthy lifestyles and the prevention of risk behaviors or other mental and somatic health problems (Manee, Khouiee, & Zaree, 2011; Pharaoh, Frantz, & Smith, 2011). Although we can find many recommendations in the literature on how specific skills should be developed to prevent Internet addiction, there is only one study (Xu, Turel, et al., 2012) that evaluated the impact of some specific skills in the prevention of Internet addiction.…”
Section: Discussionmentioning
confidence: 99%
“…The data was used to test the converse assumption that engagement in HRBs was a function of lifeskills or lack thereof. The results of the regression analyses were published in Pharaoh, Frantz and Smith [15]. The results indicated that reported capacity in identified life skills domains could significantly predict engagement in high frequency HRB (smoking, drinking, drug use, sexual activity).…”
Section: Framework For the Studymentioning
confidence: 98%
“…Therefore, it would be immensely beneficial if these life-saving skills were introduced at places of employment and learning. Pharaoh, Frantz and Smith ( 2011 ) report that life skills are a group of psychosocial competencies and interpersonal skills that help adolescents make informed decisions and deal effectively with the demands and challenges of everyday life. Life skills, according to Hawkins et al ( 1999 ), are a great way to empower adolescents to make educated and responsible decisions about their own lives and well-being, which may be directed toward personal actions.…”
Section: Introductionmentioning
confidence: 99%